電離放射線の線源、影響およびリスク原子放射線の影響に関する国連科学委員会 2022 UNSCEAR 2020年/2021年国連総会報告書 第II巻 - United Nations Scientific Committee on the Effects of Atomic Radiation (United Nations, 2022)
The United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) established by the General Assembly in 1955 assesses the levels and effects of exposure to ionizing radiation on human health and the environment. This is the second of four volumes of scientific annexes that provides the supporting scientific deliberations for the UNSCEAR 2020/2021 report to the United Nations General Assembly. Annex B “Levels and effects of radiation exposure due to the accident at the Fukushima Daiichi Nuclear Power Station: implications of information published since the UNSCEAR 2013 Report” summarizes all relevant scientific information (peer reviewed literature and monitoring data) available up to the end of 2019. These data relate to the levels and effects of radiation exposure due to the accident at the Fukushima Daiichi Nuclear Power Station. The aim of the report is to provide a summary of all scientific information and an appraisal of the implications of this information for the UNSCEAR 2013 Report.